Internet cross-domain end-to-end quality monitoring and trouble location scheme - Yongming YAN; Bing CHEN; Wenjie XU (Dianxin kexue)
With the rapid development of internet,the internet content providers needmuch better quality of internet.They usually need to deploy their applications in the internet data centers all oveRthe country due to their business requirements.Users usually cross domain to access in their data centers.So internet content providers have high level of requirements for cross-domain internet quality.It is very important for internet service providers to establish amonitoring system which couldmonitor end-to-end cross-domain internet quality and locate the troubles of network out of autonomous systems rapidly.The commonly used networkmonitoring technology and the hash algorithm in equal-costmultipath routing were analyzed.A solution of using Hash algorithm to realize full traversal of network paths andmonitor end-to-end cross-domain internet quality,was presented.Some suggestions were also given foRtrouble location scheme.